2018
DOI: 10.1007/s00404-018-4823-4
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of folic acid in pregnancy and the risk of preeclampsia and gestational hypertension: a meta-analysis

Abstract: ObjectivesWe aimed to systematically assess the relationship between folic acid supplementation in pregnancy and risk of preeclampsia and gestational hypertension.MethodsThe relevant studies were included by retrieving the Embase, PubMed and Cochrane library databases. Data extraction was conducted by two investigators independently. The risk ratio (RR) and 95% confidence interval (CI) were used as effect indexes to evaluate the relationship between folic acid supplementation and risk of gestational hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 44 publications
(54 reference statements)
4
26
0
7
Order By: Relevance
“…5,8 DNA methylation can play a key role in local control of gene expression. 8 This study also supported by research conducted by Liu, et al 2018 that foud supplementation of multivitamins containing folic acid during pregnancy could ignificantly lower preeclampsia risk. 15 Modification of gene expression can also occur due to changes in regulatory function in histones, especially in the terminal amino groups that are susceptible to changes in posttranslation modification such as methylation, acetylation, phosphorylation and ubiquitination.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…5,8 DNA methylation can play a key role in local control of gene expression. 8 This study also supported by research conducted by Liu, et al 2018 that foud supplementation of multivitamins containing folic acid during pregnancy could ignificantly lower preeclampsia risk. 15 Modification of gene expression can also occur due to changes in regulatory function in histones, especially in the terminal amino groups that are susceptible to changes in posttranslation modification such as methylation, acetylation, phosphorylation and ubiquitination.…”
Section: Discussionsupporting
confidence: 63%
“…8 This study also supported by research conducted by Liu, et al 2018 that foud supplementation of multivitamins containing folic acid during pregnancy could ignificantly lower preeclampsia risk. 15 Modification of gene expression can also occur due to changes in regulatory function in histones, especially in the terminal amino groups that are susceptible to changes in posttranslation modification such as methylation, acetylation, phosphorylation and ubiquitination. Changes in the methylation pathway that cause a decrease in protein synthesis and methylation of DNA result in abnormalities of vascular smooth muscle proliferation and increase lipid peroxidation.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…(e.g., multivitamins supplementation in trimester II–III and socioeconomic factors). Some of the causes of iron deficiency mentioned include, the deficiency of folic acid, vitamin B12, and Vitamin A [27,33,34]. Research has shown that deficiencies of iron and vitamins (E, C, D, A, B, and folic acid) can induce inflammations in the placenta [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 13 cohort studies and one randomized clinical trial, overall involving 309882 pregnant women, showed that supplementation with multivitamins containing folic acid during pregnancy significantly lowers pre-eclampsia risk (RR = 0.69, 95%CI: 0.58; 0.83) but not the risk of gestational hypertension (RR = 1.19, 95%CI: 0.92; 1.54) [26]. However, the Folic Acid Clinical Trial (FACT) recently failed to demonstrate that supplementation with 4 mg/day folic acid beyond the first trimester of gestation prevents pre-eclampsia in women at high risk for this condition (n = 2464; RR = 1.10, 95%CI: 0.90; 1.34) [27].…”
Section: Folic Acidmentioning
confidence: 99%